Perspectives of Care Experienced Young People Regarding Their Academic Experiences in Further Education - Howard, Kirstie; MacQuarrie, Sarah (Frontiers in Education, 2022)
Background. The academic attainment of care experienced young people (CEYP) is consistently reported as below the national average (Scottish Government, 2018a). Studies draw on associations between low academic attainment and poor life outcomes (Connelly & Matheson, 2012). Most research relating to CEYP and education has highlighted the impact barriers and opportunities arising from education can have on their attainment. Although, this research is almost exclusively concerned with schooling up to aged 16 (Sugden, 2013). Few studies have explored the perspectives and experiences of CEYP in further education, especially in a Scottish context (Morrison & Shepherd, 2015). Aim. This study aimed to centralise the views of CECYP to gain insight into their achievement opportunities and barriers in FE and to inform support services for CEYP. Sample. Ten CEYP, aged 16-24, studying at a further education college in Scotland participated in the study. Seven further education colleges from geographically diverse regions are represented. Methods. CEYP participated in semi-structured interviews to share their experience of further education. Findings. Thematic analysis was used to produce the following main themes: Care experience and personal narratives, valuing further education and navigating support systems. Conclusions. The findings largely reflect current literature. Perceived opportunities for FE achievement included stability of education and accommodation, personalised and financial support and supportive relationships. Reported barriers included care-related challenges, additional support needs, staff knowledge and labelling practices. Priorities for support service development included increased CEYP informed and led services such as peer mentoring, corporate parenting training and peer education. Implications for FE practice and future research are discussed.